Numerical realization of a semi-active virtual acoustic black hole effect - Soleimanian, Sina; Petrone, Giuseppe; Franco, Francesco; De Rosa, Sergio; Kołakowski, Przemysław (Frontiers in Mechanical Engineering, 2023)
Noise mitigation by means of the acoustic black hole (ABH) effect is a well-known engineering solution. However, the conventional method of applying ABH effect which requires modification of the structure geometry has various limitations which encourage the research of virtual ABH concept. In this study, the effect of ABH was applied through introducing virtual stiffness by a shunt circuit. According to the force-voltage electric analogy, stiffness has an inverse relationship with capacitance. So that the ABH effect can be virtually realized by follow a power law profile using an array of independent capacitive shunts. The concept is studied through finite element simulation developing a macro code in APDL. To evaluate the influence of capacitance profile on the acoustic radiated power, parametric studies are conducted. Based on the results of the parametric studies, the capacitance profile is tuned for minimum radiated power. It is revealed that the virtual ABH effect can be used for multi-mode isolation of structure-born noise if semi-actively tuned.